PTU-050 Addressing The Issue of Indeterminate Interferon Gamma Release Assays Prior to Biologic Therapy in Patients with Inflammatory Bowel Disease Patients. (17th August 2016) - Thi, AA; Bouri, S; Wolfson, P; Owen, L; Abbara, A; John, L; Davidson, RN; Hart, AL
Abstract : Introduction: Biologic treatment has improved outcomes of patients with complex inflammatory bowel disease (IBD). Anti-TNF therapy is associated with a fivefold increased risk of reactivation of tuberculosis (TB). When TB occurs, it is commonly extra-pulmonary and disseminated with an atypical presentation and can be diagnostically challenging. An indeterminate interferon gamma release assay (IGRA) result occurs in <2% of the healthy population, however this is higher in immunosuppressed patients. Given the increased risk of TB, screening for latent TB infection (LTBI) remains vital before commencing biologics. Methods: All IBD patients who had an IGRA test between July 2013 and November 2015 before commencing biologic therapy were identified from the high cost funding database held in the Pharmacy Department at St Mark's Hospital. Clinical and electronic case records were reviewed. Results: 247 patients were screened for TB with an IGRA test during the study period. The mean age was 36.9 years (range 8–85), 54% were male and 70% had Crohn's disease. 78 patients (32%) had an indeterminate IGRA result and 35/78 (45%) patients had a repeat test; 17/35 (49%) had a second indeterminate results and the remaining 18 /35 (51%) had a negative test. 8/78 with an indeterminate test had a Mantoux as per our algorithm; 3 were positive, 4 were anergic and 1 was negative. Of the 247 patients, 210 patients received biologic treatment. Thirty-two patients (15%) delayed receiving their biologic treatment for various reasons, including receiving LTBI treatment. Of 210 patients, 158 patients (75%) had Infliximab, 38 patients (18%) had Adalimumab, 13 had Vedolizumab and 1 had Golimumab. 30 patients were referred for an infectious diseases opinion; 7 with a positive IGRA and 7 with a negative IGRA but abnormalities on their chest X-ray and a high epidemiological risk for TB. One patient who had an indeterminate IGRA result developed active TB during the study period. Conclusion: Almost one third of IBD patients had an indeterminate IGRA with half of those having a second indeterminate result. Sampling and processing factors also influence the prevalence of indeterminate results in this population. This supports risk stratification with more weight added to the risk than IGRA alone. Reactivation of LTBI may lead to delays in starting treatment hence it is vital to take into account the patient's pre-test probability of LTBI before using an IGRA to avoid such delays. Reference: 1 Wong H, Ip M, Tang W, et al . Performance of the interferon-gamma release assay for Tuberculosis screening in inflammatory Bowel disease patients. IBD 2014;20 (11):2067–2072. Disclosure of Interest: None Declared